Exosomes: The role in mammalian reproductive regulation and pregnancy-related diseases - Guo, Xing-Ru; Ma, Yun; Ma, Zi-Ming; Dai, Tian-Shu; Wei, Shi-Hao; Chu, Yuan-Kui; Dan, Xin-Gang (Frontiers in Physiology, 2023)
Exosomes are secreted by different kinds of mammalian cells and have the ability to transport a variety of biomolecules, including proteins, lipids, and nucleic acids, which can act on target cells to produce biological effects. Exosome research has been more significant in recent years due to its potential use in treating diseases like cancer, neurological disorders, and immune disorders. Meanwhile, recent studies have shown that exosomal contents, especially miRNAs, have been implicated in numerous physiological processes related to reproduction, while its role is more important in regulating mammalian reproduction and pregnancy-related diseases. The article focuses on the role of exosomes in follicular development, early embryonic development, embryonic implantation and the development of pregnancy-related diseases in human and animals, as well as the origin, composition and intercellular communication of exosomes, establishing the foundation for revealing the mechanism of exosomes in the regulation of mammalian reproduction, and also presenting new approaches and ideas for the research, especially in diagnosis and treatment of pregnancy-related diseases.